The effect of colloids practicum e-module to improve students’ interest on virtual lab during the covid-19 pandemic - Nelius Harefa; Novia Fransisca Dewi Silalahi; Leony Sanga Lamsari Purba; Herna Febrianty Sianipar (Jurnal Pendidikan Kimia (JPKim), 2021)
Practical learning which is generally carried out in the laboratory is one of the important lessons in the science learning process, especially chemistry. The Covid-19 pandemic has caused practical learning activities to not be accommodated in real laboratories. This situation encourages the creation of practical learning innovations, namely the use of virtual labs. In this study, students' learning interest in the use of virtual labs is described which is integrated with the use of e-modules on colloidal material. Based on the results of data analysis, 74.55% of students were interested in using the virtual lab, 10.90% very interested, 12.73% quite interested, and 1.82% lack of interested. These data indicate that the majority of students can make good use of the virtual lab and are able to optimally elaborate on the learning process. However, virtual labs are not intended to replace real laboratories but can be used as supplements and media to support learning in real laboratories.Keywords: Colloids, Practicum, e-module, Virtual Lab